32=-4(k-6)

Simple and best practice solution for 32=-4(k-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 32=-4(k-6) equation:


Simplifying
32 = -4(k + -6)

Reorder the terms:
32 = -4(-6 + k)
32 = (-6 * -4 + k * -4)
32 = (24 + -4k)

Solving
32 = 24 + -4k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '4k' to each side of the equation.
32 + 4k = 24 + -4k + 4k

Combine like terms: -4k + 4k = 0
32 + 4k = 24 + 0
32 + 4k = 24

Add '-32' to each side of the equation.
32 + -32 + 4k = 24 + -32

Combine like terms: 32 + -32 = 0
0 + 4k = 24 + -32
4k = 24 + -32

Combine like terms: 24 + -32 = -8
4k = -8

Divide each side by '4'.
k = -2

Simplifying
k = -2

See similar equations:

| 7-18=4y-3y+4 | | 3(5x-180+45)=-4(x-72) | | 52x(x-7)=43 | | -2(x+8)=36 | | g(2)+4g-32=0 | | 2-5x+6=14x-32+10(2-x) | | Y=-7/8-9/8 | | X/4-10=-4 | | 6m-13=47 | | (3y+2)+(2y+13)= | | 4x-7-36=0 | | 3m+(5+m)+5= | | 7(5+3r)=203 | | 4y-9=10 | | 4.25/0.75 | | 4x-7+6x=13-10 | | (x+4)(x+5)=1 | | x+10-15=0 | | 14+5x+2x=49 | | 2.840=1.2x-0.2x^2 | | -8y-7=9 | | 3(y+2)=2y+13 | | 7n+8n=-33 | | -8-2x+13=11+5x+57 | | 2x+17=-(3-7x) | | 4-4*5+4= | | 1.64=0.5x-0.2x^2 | | 9x^3+6x^2-9x=0 | | 12-1.5x/3 | | 3y+2=2y+13 | | -1/5b-2/5=-5 | | 250/298=x/368 |

Equations solver categories